Identification of three novel pathogenic ITGA2B and one novel pathogenic ITGB3 mutations in patients with hereditary Glanzmann's thrombasthenia living in Eastern Turkey. (17th February 2021) - Karaman, Kamuran; Yürektürk, Eyüp; Geylan, Hadi; Yaşar, Akkız Şahin; Karaman, Serap; Aymelek, Huri Sema; Çetin, Mecnun; Oner, Ahmet Fayik
Abstract: Glanzmann's thrombasthenia (GT) is an autosomal recessive disorder in which the underlying problem is the lack or dysfunction of the GpIIb/IIIa receptor on the platelet surface. The present study determines the genetic mutation typology and analyzes the association between mutation types and clinical findings in patients diagnosed with GT who were followed up in Department of Pediatric Hematology of the Yüzüncü Yıl University School of Medicine. The medical charts of 17 patients who underwent therapy and that were followed up in the Department of Pediatric Hematology of the Yüzüncü Yıl University Dursun Odabaş Medical Center between January 2008 and April 2018 were reviewed retrospectively. Data on such patient characteristics as present genetic mutations, age, gender, age at diagnosis, presenting symptoms, clinical findings, and platelet count and volume were garnered from the patient records. Of the 12 patients identified with genetic mutations, six had the same type of mutation, while four were identified with novel mutations that have to date not been defined in literature. Of these four mutations, three were located in the ITGA2B gene and one in the ITGB3 gene. The present study identified no significant association between the genetic and clinical findings of the patients. Novel mutations were identified in four cases in the present study. No association was found between the mutation type, and the bleeding scores and bleeding phenotypes of the patients. Further studies involving a larger number of patients are required to determine the relationship between the genotypes and clinical findings in patients with GT.